A Spanish framework for school principal and professional identity: Context, development and implications - Bolívar, Antonio (Education Policy Analysis Archives, 2019)
The context of school leadership in Spain (low stability, professional identity, lack of pedagogical leadership) is described, as well as the reasons that led to the directors themselves, grouped by the Federations of their regional Associations (FEDADi, FEDEIP, FEAE), to considerer it necessary to develop a “Spanish Framework for Good School Principalship” (MEBD) in the last two years (2016-2018). But, beyond this, along with other factors, we want to highlight the context to which the Framework responds and the functions it can play to enhance the pedagogical leadership of school administration. From a comparative and global perspective, the relationships between the Spanish Framework and other Ibero-American (Chile and Peru) and Anglo-Saxon frameworks are described, as well as the structure and content of the Spanish Framework itself. The meaning and functionality that the MEBD can represent to visualize a professional identity of the school management is analyzed, while demanding professionalism, as a specific practice that must be carried out in accordance with the competences and standards specified by the MEBD. Beyond changing regulations, at the discretion of political decisions, the MEBD aspires to be configured as a stable reference, as internal regulation of the profession, in the manner of deontological codes of good practices. In its implications, this Framework requires and demands, in parallel, structural conditions (resources, autonomy, professionalization) so that a good principalship would be possible. At the same time, it aims to guide the processes of selection, training (initial and permanent), evaluation of the principalship and its recognition.